Research on the Optimization Strategy of the Speed Ratio Control Parameter of Vehicle Swing Pin Chain CVT - Guo Wei; Li Yuankai; Zhang Wu; Jia Gaoxiang (Jixie chuandong)
Speed ratio control is one of the key technologies in transmission control field. The fuzzy PID control method is adopted to simulate the automobile cycle working condition by analyzing the structure and working principle of the swing pin chain CVT，the mathematical model of the CVT transmission system and the sub-model of the speed ratio fuzzy controller are built. The fuzzy control is simulated based on the Simulink/Cruise co-simulation software platform. Finally，genetic algorithm is introduced to optimize the control rules of the speed ratio controller，and the speed ratio tracking strategies of the starting and cycling conditions are verified respectively. The results show that the speed ratio fuzzy control based on genetic algorithm is better than the traditional fuzzy PID control method in the following effect and error variation of the target speed ratio，and meets the requirements of the swing pin chain CVT speed ratio control.